The influence of the ideology of nationalism on the activities of modern French far-right - Hryshel, Aliaksei M. (Journal of the Belarusian State University. History, 2018)
The article discusses the influence of the ideology of nationalism on the activities of modern French far-right. The focus of the article are the practical activities of such parties and organizations as the National Front, Bloc identitaire, Action française and Renouveau français, which reflect the main directions of the french far-right movement. Their ideological basis is analyzed. The author revealed the differences between the ideologies of nationalism, nazism and fascism, because in the literature these terms are often confused with each other. The discovered trend of changes in the content of the term «ethnos» which influences the establishment of which parties and organizations use racist slogans is very important. It was established that the modern french far-right is hard to blame in the direct manifestation of extreme forms of nationalism, because there isn’t clear understanding of the difference between some terms. The results of the study can be used in the lecturing of courses in political science, history of France and political parties.
Keywords: far-right; National Front; Bloc Identitaire; nationalism; racism; nazism; fascism; immigrants